Innovation In City Security Governance In The Implementation Of Cctv And Command Center On Ahmad Yani Street, Makassar City - Reviananda Nasir; Andi Cudai Nur; Herman H (Universitas Negeri Makassar, 2026)
This study examines the diffusion of the CCTV and Command Center system in Makassar within the framework of Rogers’ Diffusion of Innovation and Smart City governance theory. While previous studies predominantly emphasize technological efficiency in smart security systems, limited attention has been given to how such innovations reshape governance structures and institutional authority. This study addresses that gap.Using a qualitative case study approach, data were collected through in-depth interviews with key stakeholders from the police institution and the Communication and Information Office (Diskominfo), supported by document analysis and triangulation techniques. Data were analyzed using the Miles and Huberman interactive model.The findings indicate that the system was adopted due to its strong relative advantage, operational compatibility, and observability in improving response time and inter-agency coordination. However, beyond operational efficiency, the study reveals that digital surveillance infrastructure centralizes authority and creates institutional dependency due to server control and infrastructure governance arrangements.This research contributes to urban governance and technology-based public administration literature by demonstrating that smart security innovation produces a hybrid digital-bureaucratic governance model, where technological modernization coexists with centralized administrative control. The study highlights the need for clearer digital authority distribution and participatory expansion to ensure balanced smart governance.